(untitled) (Jurnal Perencanaan Pembangunan: The Indonesian Journal of Development Planning, 2025)
Aloe vera is an effective and efficient plant that grows in Pontianak City because of its suitable geographical conditions. Aloe vera is an agricultural plant or biopharmaceutical plant that has various benefits. However, the use of aloe vera is still limited, and not many business actors have developed aloe vera into various processed products with economic value, even though the potential and benefits of aloe vera are very diverse, and even aloe vera is a creative economic product that can be developed by MSMEs. This prompted the city government to issue Pontianak City Regional Regulation Number 5 of 2015 to support the development of aloe vera products. Therefore, this study intends to find out how to overcome problems in developing Pontianak City’s flagship product, namely aloe vera; a comprehensive analysis is needed through evidence-based policy concepts. By conducting a study through the concept of the Pew-MacArthur with five research focuses, namely program assessment, budget development, implementation supervision, results monitoring, and targeted evaluation. The purpose of this study is to find out the implementation and evidence-based policies to encourage one of the leading commodities of the city of Pontianak, namely aloe vera, can be used by MSMEs in various creative and value-selling products to support economic growth, create jobs, increase the income of the surrounding community, and support exports with a wider reach. Qualitative descriptive research is a method used with data collection techniques through interviews, observations, literature studies, and documentation. The results of the study show that to improve the welfare of the community, local governments, especially the Trade Micro Business Cooperative Office and the Pontianak City Agriculture and Fisheries Office, have succeeded in organizing, directing, and developing aloe vera as a regional superior product. This development is carried out through an MSME program that focuses on the creative economy, which includes innovations in the planning, production, and marketing of aloe vera.